Mitochondrial Dysfunction Associates With Acute T Lymphocytopenia and Impaired Functionality in COVID-19 Patients - Mo, Yufei; To, Kelvin Kai-Wang; Zhou, Runhong; Liu, Li; Cao, Tianyu; Huang, Haode; Du, Zhenglong; Lim, Chun Yu Hubert; Yim, Lok-Yan; Luk, Tsz-Yat; Chan, Jacky Man-Chun; Chik, Thomas Shiu-Hong; et al. (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection results in rapid T lymphocytopenia and functional impairment of T cells. The underlying mechanism, however, remains incompletely understood. In this study, we focused on characterizing the phenotype and kinetics of T cell subsets with mitochondrial dysfunction (MD) by multi-color flow cytometry and investigating the association between MD and T cell functionality. While 73.9 % of study subjects displayed clinically lymphocytopenia upon hospital admission, significant reduction of CD4 or CD8 T cell frequency was found in all asymptomatic, symptomatic and convalescent cases. CD4 and CD8 T cells with increased MD were found in both asymptomatic and symptomatic patients within the first week of symptom onset. Lower proportion of memory CD8 T cells with MD was found in severe patients than in mild ones at the stage of disease progression. Critically, the frequency of T cells with MD in symptomatic patients was preferentially associated with CD4 T cell loss and CD8 T cell hyperactivation, respectively. Patients bearing effector memory CD4 and CD8 T cells with the phenotype of high MD exhibited poorer T cell responses upon either PMA/Ionomycin or SARS-CoV-2 peptide stimulation than those with low MD. Our findings demonstrated an MD-associated mechanism underlying SARS-CoV-2-induced T lymphocytopenia and functional impairment during acute phase of infection.